2016
DOI: 10.21474/ijar01/990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed and Fertilizers on the Growth and Body Composition of Air Breathing Fishes Channa Striata and Pangasius Hypophthalmus Fry.

Abstract: Experiments were conducted to evaluate the response of five treatments to observe the growth performance and meat composition of Channa striata and Pangasius hypophthalmus advanced fry for the period of 60 days. Composition of nitrogen in different experiments treatment with different combinations of supplementary feed. The pond was supplemented with 0.2g N/100g body weight fertilizers and supplementary feed, the source of which are different. The treatment was cow dung, pig dung, nitrophos, supplementary feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Our results for protein contents showed a signi cant difference (P<0.05) among groups. Panchakshari et al (2016) observed feed and fertilizer effects on the composition of Channa striata and P.hypophthalmus and found a signi cant difference (P<0.05) between the body compositions of these sh species. The amount of crude protein depends on natural and supplementary feed contents.…”
Section: Proximate Analysismentioning
confidence: 91%
“…Our results for protein contents showed a signi cant difference (P<0.05) among groups. Panchakshari et al (2016) observed feed and fertilizer effects on the composition of Channa striata and P.hypophthalmus and found a signi cant difference (P<0.05) between the body compositions of these sh species. The amount of crude protein depends on natural and supplementary feed contents.…”
Section: Proximate Analysismentioning
confidence: 91%